Factors Analysis that Affecting the Intention to Use Digital Payment (Case Study on OVO Users in Jakarta, Bogor, Depok, Tangerang, Bekasi) - Indar Rachmawati, Wahyu; Rustandi Kartawinata, Budi; Wijayangka, Candra; Hasbi, Imanuddin (KnE Social Sciences, 2020)
Transaction activities have evolved from cash payments to non-cash payments. The digital payment is a method of payment made using electronic media. Payments can be made through short message service, mobile banking, internet banking, e-money, or e-wallet. This study shows how response of OVO users in Jakarta, Bogor, Depok, Tangerang, and Bekasi ( Jabodetabek) to the intention of use digital payments which have become a trend in carrying out transactions of anything practically. This research uses quantitative methods. The research data was obtained through the distribution of google docs online questionnaires which were shared through social media. The sample of this study is OVO users in Jabodetabek with a total of 200 respondents with a percentage of 76% having experience of using e-wallet services. The results showed that the Performance Expectancy, Effort Expectancy, and Perceived Security factors were significantly affecting the intention to use digital payment (OVO) in Jabodetabek. While the Social Influence and Culture factors do not affect significantly the intention to use digital payment (OVO) in Jabodetabek. Keywords: digital payment, performance expectancy, effort expectancy, perceived security